Distribution of shallow NV centers in diamond revealed by photoluminescence spectroscopy and nanomachining. (15th October 2020) - Fazeli Jadidi, Majid; Özer, H. Özgür; Goel, Saurav; Kilpatrick, Jason I.; McEvoy, Niall; McCloskey, David; Donegan, John F.; Cross, Graham L.W.
Abstract: We performed nanomachining combined with photoluminescence spectroscopy to understand the depth distribution of nitrogen-vacancy (NV) centers formed by low energy nitrogen ion irradiation of the diamond surface. NV − and NV 0 fluorescence signals collected from the surface progressively machined by a diamond tip in an atomic force microscope (AFM) initially rise to a maximum at 5 nm depth before returning to background levels at 10 nm. This maximum corresponds to the defect depth distribution predicted by a SRIM simulation using a 2.5 keV implantation energy per nitrogen atom. Full extinguishing of implantation produced NV − and NV 0 zero phonon line peaks occurred beyond 10 nm machining depth, coinciding with the end of easy surface material removal and onset of significant tip wear. The wear ratio of for NV active, ion irradiated diamond compared to the single-crystal diamond tip was surprisingly found to be 22:1. The reported results constitute the first integrated study of in-situ machining and wear characterization via optical properties of the diamond surface containing shallow formed NV centers. We discuss possible metrology applications for diamond tools used in precision manufacturing. Graphical abstract: Image 1